Social Justice and Human Rights: A Legal Perspective - Setiawan , Andri Herman; Sunandar, Firman Nurdiansyah; Fajar, Ahmad (Politeknik Siber Cerdika Internasional, 2025)
Background: Social justice and human rights are fundamental principles shaping contemporary legal systems. Nevertheless, their implementation often faces obstacles arising from structural inequality, economic disparity, and the exclusion of marginalized groups. Legal frameworks play a crucial role in operationalizing these principles within society Objective: This study seeks to examine the legal dimensions of social justice and human rights by analyzing their conceptual foundations, international legal instruments, and application in national legal systems, with a focus on equality, non-discrimination, and access to justice Methods: The research employs a doctrinal legal method through the analysis of international human rights treaties, national legislation, judicial decisions, and relevant academic literature. A normative and conceptual approach is used to explore the relationship between social justice theories and human rights law Results: The findings indicate that international human rights law provides a comprehensive normative framework to support social justice. However, inconsistencies in national implementation, limited institutional capacity, and socio-economic conditions continue to hinder effective legal protection for vulnerable and marginalized groups Conclusion: The study concludes that a rights-based legal approach is essential for addressing structural inequalities. Strengthening legal institutions and ensuring alignment between national laws and international human rights standards are key to advancing social justice